Spy x Family - Vol 1 Mission 1. 1 - Endo, Tatsuya; Loe, Casey; Yu, Amy. (San Francisco, CA : Viz Media LLC, 2020)
"Master spy Twilight is the best at what he does when it comes to going undercover on dangerous missions in the name of a better world. But when he receives the ultimate impossible assignment--get married and have a kid--he may finally be in over his head! Not one to depend on others, Twilight has his work cut out for him procuring both a wife and a child for his mission to infiltrate an elite private school. What he doesnt know is that the wife hes chosen is an assassin and the child hes adopted is a telepath!"--Page [4] of cover.
Rated T+, for older teen.
Keywords: Spies -- Comic books, strips, etc; Psychic ability -- Comic books, strips, etc; ANYA; YOR BRIAR; SHONEN; SECRETS; THORN PRINCESS; SECRET IDENTITY; ASSASSIN; FAKE FAMILY; COMEDY; COLD WAR; ELITE SCHOOL; MIND READING; TWILIGHT; FRANKIE; MISSION IMPOSSIBLE; SPY; ACTION; LOID FORGER; TELEPATH; Graphic novels